Concentrações de ácido giberélico e períodos de estratificação na emergência do porta-enxerto de marmeleiro 'Japonês' (Chaenomeles sinensis) - Pio, Rafael; Dalastra, Idiana Marina [UNESP]; Abucarma, Vânia Márcia; Campagnolo, Marcelo Angelo; Dranski, João Alexandre Lopes; Pinto Jr., Artur Soares (FapUNIFESP (SciELO), 2010)
The objective of this study was to evaluate the influence of gibberellic acid (GA3) and cold stratification of Japonese quince tree seeds (Chaenomeles sinensis), on the growth of rootstock seedlings. Seeds were collected from fruits, rinsed in water, and dried for 48 hours. Soon after, the seeds were submerged in different gibberellic acid concentrations: 0, 100, 200 and 300 mg L-1, for 24 hours, with an oxygenation system. The seeds were placed in Petri plates between moistened cotton and submitted to cold stratification in a B.O.D. chamber (at 4 °C) for different periods (0, 20, 40 and 60 days). At the end of each period, the seeds were distributedin polystyrene trays containing 72 cells, with vermiculite as substrate. After 30 and 60 days, the percentage emergence was measured and at the end of 60 days, the mean length of the seedlings and mean dry mass were determined. It was concluded that the seeds of Japanese quince should be treated with 200 mg L-1 of GA3 and stratified in humidified cotton for 60 days.
Gibberellic acid concentrations and the stratification on emergence of quince tree rootstock (Chaenomeles Sinensis)
Keywords: GA3; Propagation; Seedlings; Seedlings production; Cydonia oblonga; Gossypium hirsutum; Pseudocydonia sinensis